Biogeography of Cyanobacterial isiA Genes and Their Link to Iron Availability in the Ocean - Li, Qian; Huisman, Jef; Bibby, Thomas S.; Jiao, Nianzhi (Frontiers in Microbiology, 2019)
The cyanobacterial iron-stress-inducible isiA gene encodes a chlorophyll-binding protein that provides flexibility in photosynthetic strategy enabling cells to acclimate to low iron availability. Here, information on the diversity and abundance of isiA genes are provided from 14 oceanic stations encompassing large natural gradients in iron availability. Synechococcus CRD1 and CRD2-like isiA genes were ubiquitously identified from tropical and subtropical waters of the Pacific, Atlantic and Indian Oceans. The relative abundance of isiA-containing Synechococcus cells ranged from under 10% of the total Synechococcus population in regions where iron is replete such as the North Atlantic subtropical gyre, to over 80% in low-iron but high-nitrate regions of the eastern equatorial Pacific. Interestingly, Synechococcus populations in regions with both low iron and low nitrate concentrations such as the subtropical gyres in the North Pacific and South Atlantic had a low relative abundance of the isiA gene. Indeed, fitting our data into a multiple regression model showed that 80% of the variation in isiA relative abundances can be explained by nitrate and iron concentrations, whereas no other environmental variables (temperature, salinity, Chl a) had a significant effect. Hence, isiA has a predictable biogeographical distribution, consistent with the perceived biological role of IsiA as an adaptation to low-iron conditions. Understanding such photosynthetic strategies is critical to our ability to accurately estimate primary production and map nutrient limitation on global scales.